PENDAMPINGAN PEMANFAATAN MEDIA PEMBELAJARAN DIGITAL CANVA OLEH MAHASISWA PLP LINTAS JURUSAN DI SMAN 2 LADONGI - Pratiwi, Sindy; Opie Oktavia, Komang; Eka Wulandari Laki Lima, Alda; Elisya Umbawan, Wafiqh; Andika, Kadek; Lestari, Desi; Subawo, Made (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low utilization of digital learning media by teachers and students in schools, particularly regarding the use of the Canva application. The study aims to describe the process of mentoring the use of Canva as a digital learning medium by interdisciplinary PLP students and to determine its impact on improving the quality of learning at SMAN 2 Ladongi. The method used is qualitative research with a descriptive approach. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions using triangulation techniques to ensure data validity. The results of the study indicate that the mentoring was implemented through the stages of planning, implementation, and evaluation. This activity was able to improve teachers’ ability to design visual-based learning media as well as enhance students’ skills, creativity, and interest in learning. In addition, PLP students also gained experience in developing pedagogical and professional competencies. Thus, the use of Canva as a digital learning medium can be an effective alternative in creating innovative and interactive learning.